2012
DOI: 10.1093/icesjms/fss076
|View full text |Cite
|
Sign up to set email alerts
|

Interannual changes in zooplankton on the West Spitsbergen Shelf in relation to hydrography and their consequences for the diet of planktivorous seabirds

Abstract: Kwasniewski, S., Gluchowska, M., Walkusz, W., Karnovsky, N. J., Jakubas, D., Wojczulanis-Jakubas, K., Harding, A. M. A., Goszczko, I., Cisek, M., Beszczynska-Möller, A., Walczowski, W., Weslawski, J. M., and Stempniewicz, L. 2012. Interannual changes in zooplankton on the West Spitsbergen Shelf in relation to hydrography and their consequences for the diet of planktivorous seabirds. – ICES Journal of Marine Science, 69: 890–901. The purpose of the work was to determine how atmospheric and oceanic processes (th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
78
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 72 publications
(88 citation statements)
references
References 58 publications
10
78
0
Order By: Relevance
“…Steen et al (2007) report consistently low numbers of Calanus glacialis AF in gular pouches, a stage that was not observed at all in net samples along a transect past the bird colony. A recent study covering a total of eight years (Kwasniewski et al 2012) showed the coupling for C. glacialis/C. finmarchicus ratio and, in support of earlier studies, they suggested that the foraging ground of the little auk is most likely limited to the Arctic water current, separated by a hydrographical front, from the Atlantic water current and not mixed water masses as in our study.…”
Section: Discrepancies Between Alle Alle Diet and Net Samplingsupporting
confidence: 92%
“…Steen et al (2007) report consistently low numbers of Calanus glacialis AF in gular pouches, a stage that was not observed at all in net samples along a transect past the bird colony. A recent study covering a total of eight years (Kwasniewski et al 2012) showed the coupling for C. glacialis/C. finmarchicus ratio and, in support of earlier studies, they suggested that the foraging ground of the little auk is most likely limited to the Arctic water current, separated by a hydrographical front, from the Atlantic water current and not mixed water masses as in our study.…”
Section: Discrepancies Between Alle Alle Diet and Net Samplingsupporting
confidence: 92%
“…Due to the evident linkage between body condition and survival (Harding et al 2011), adult birds should govern the degree of parental investment against the negative consequences on their own body condition. Exploring the mechanisms that regulate the parental investment might help to evaluate the trade-offs involved in the reproductive performance in Little Auks, which are particularly important in predicting their response to the worsening foraging conditions in the Arctic Kwasniewski et al 2012). …”
Section: Introductionmentioning
confidence: 99%
“…The net zooplankton catches described by Jakubas et al (2013) in the same area (Arctic-type waters, the Hornsund area) and at the same period as our study (the end of July) showed that C. glacialis represented 70% of the older life stages (CIV, CV and adults) of both mentioned Calanus species and that the fifth copepodite of C. glacialis constituted half of this amount. Moreover, multiyear observations conducted by Kwasniewski et al (2012) showed the substantial domination of C. glacialis older copepodite stages over C. finmarchicus in the Arctic shelf community at this time of the year.…”
Section: Discussionmentioning
confidence: 87%
“…This study provides only high-resolution LOPC measurements -information about zooplankton species composition is based on numerous previous studies conducted in the same study area (e.g., Kwasniewski et al 2010;Kwasniewski et al 2012;Jakubas et al 2013;Stempniewicz et al 2013;Trudnowska et al 2014;Trudnowska et al 2015;Trudnowska et al 2016). Using the abundance estimates and size structure data derived from the LOPC, we grouped plankton into two size fractions: a small size fraction (0.25-1.0 mm ESD), consisting of, e.g., Calanus nauplii, Oithona spp., Microcalanus spp., Pseudocalanus spp., and a large size fraction (1.0-2.5 mm ESD) -hereafter Calanus -represented predominantly by the older life stages (CIV, CV, adult) of Calanus spp.…”
Section: −3mentioning
confidence: 99%
See 1 more Smart Citation